Increasing Scientific Literacy using a Guided Inquiry Approach assisted by PhET Simulations in Wave Material - Marwanti, Kissi; Marina, Dewi; Astra, I Made (Jurnal Penelitian Pembelajaran Fisika, 2024)
This research was conducted to assess the growth of students' scientific literacy skills using the Guided Inquiry learning model assisted by PhET Simulation on Wave material. The method used in this research is Penelitian Tindakan Kelas (PTK) or Action Research with the research subjects were 39 students of SMA Negeri 6 Kabupaten Tangerang class XI MIPA 3. This research design consists of three cycles with each cycle consisting of four stages: planning (plan), implementation (action), observation (observe), and reflection (reflect). The results of the research show that the application of the Guided Inquiry learning model assisted by PhET Simulation can improve students' scientific literacy abilities with the average percentage value of scientific literacy abilities in the "good" category, this can be seen in the greatest increase that occurred in cycle III, which was found The average percentage increase in the science content indicator was 68.7%, the science context indicator was 63.7%, and the science process indicator was 65.5%. From the results of observations from this research, it can be seen that through the Guided Inquiry learning model assisted by PhET Simulation, students are more active in the learning process.